1977
DOI: 10.1002/ijc.2910200216
|View full text |Cite
|
Sign up to set email alerts
|

Expression of alien h‐2 specificities on a chemically induced balb/c fibrosarcoma

Abstract: The presence of alien histocompatibility antigens on the cell surface of the 3-methylcholanthrene-induced BALB/c (H-2d) fibrosarcoma C-1, was investigated by serological and transplantation studied. Absorption experiments with monospecific alloantisera showed that C-1 cells expressed their original private (H-2.4 and 31) and public (H-2.3, 8, 28, and 35) specificities. C-1 cells were also able to absorb monospecific antisera directed to the private specificity H-2.23 of the H-2k haplotype, as well as antisera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…The presence of 'foreign' allospecificities in MC sarcomas has been previously docu mented by Meschini et al [6] and has been interpreted as though they represent the tu mor-specific antigens [7] or that they are as sociated antigens different from those which are tumor specific [23]. It should be noted that anti-MC25 sera is capable of blocking the reactivity of anti-H-2D.13 and anti-H-2D.16 sera on lymphoma cells, both antigens detected on the surface of the MC25 sarcoma cells as 'foreign' [Merino, F.; unpublished observations].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of 'foreign' allospecificities in MC sarcomas has been previously docu mented by Meschini et al [6] and has been interpreted as though they represent the tu mor-specific antigens [7] or that they are as sociated antigens different from those which are tumor specific [23]. It should be noted that anti-MC25 sera is capable of blocking the reactivity of anti-H-2D.13 and anti-H-2D.16 sera on lymphoma cells, both antigens detected on the surface of the MC25 sarcoma cells as 'foreign' [Merino, F.; unpublished observations].…”
Section: Discussionmentioning
confidence: 99%
“…By these tests, antigeneic individuality or cross-reactivity of the tumor-specific anti gens among different chemically induced tu mors has been reported [2][3][4], H-2 allospecificities of these tumors have been studied by either complement-de pendent cytotoxicity techniques in cultured cells or by the absorption of specific alloantisera with these tumors. H-2 alloantigen ex pression on neoplastic cells seems to play a role in tumor immunity mechanisms since new alloantigens can be detected on the surface of these cells and their possible role as tumorspecific antigens has been postulated [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, several examples are available to elucidate the possible non-MHC genetic control of the expression of MHC-encoded cell recognition, of interaction molecules (Rich et al 1977), and of MHC-encoded suppressor functions (Albright et al 1977, Meruelo et al 1977, Silver and Lane 1977. It should be noted that the TATA involved in the present study is a unique antigenic structure, cross-reacting with the TATA of only one out of five other C sarcomas of the same etiology (Meschini et al 1977). The tumor whose TATA cross-reacted with that of C-1 was a BALB/c/Dp sarcoma (ST2) with no detectable H-2k-like foreign antigens.…”
mentioning
confidence: 91%
“…Recently, a number of observations have suggested that certain tumor cells and virally infected cells may express alien antigens identified with the major histocompatibility locus of an unrelated haplotype (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). These observations have involved the ability of tumor cells to absorb cytotoxic antibody against normal cells of an unrelated haplotype (4), the ability of alloantisera directed against H-2 antigens of an inappropriatehaplotype to lyse cells (7,10), or the unexpected growth of a tumor in immunized hybrid (1,2) or recombinant animals (6).…”
mentioning
confidence: 99%
“…Although originating in an H-2d strain mouse, this tumor apparently expresses, in addition to its normal complement of histocompatibility antigens, antigenic specificities associated with the H-2Kk gene product (4). Appropriate absorption experiments ruled out the possibility that the ability of these cells to absorb anti-H-2k antisera was due to viral antigens or previously undetected public specificities (4). Furthermore, syngeneic mice immunized against the C-1 tumor produce antisera having properties identical to anti-H-2Kk antisera produced in congenic mice (5).…”
mentioning
confidence: 99%